Peranan Trimetazidine pada Reperfusion Injury - Taka Mehi; Yoga Yuniadi; Nur Haryono (Jurnal Kardiologi Indonesia, 2015)
The incidence rate of ST-Elevation acute Myocardial Infarct (STEMI) keeps increasing. Currently, myocardial reperfusion, either with thrombolytic or Primary Percutaneous Coronary Intervention (PPCI), is the main treatment. However, mortality rate of STEMI patients undergoing PPCI is still high which is 6% to 14%. The main purpose of PPCI is to restore the patency of infarcted epicardial artery and to establish microvascular reperfusion as soon as possible so that it can reduce enlargement of irreversible necrotic myocardial tissue. In the other hand, restored patency of infarcted epicardial artery does not indicate sufficient reperfusion to microvascular. Such phenomenon is called no-reflow or microvascular obstruction (MVO). Specific pathogenic component of MVO is reperfusion injury. Reperfusion injury involves some mediator and mechanisms, one of which is the process of thrombolysis and angioplasty. Mediator that play a certain role is inflammatory neutrophil which is activated and accumulated. Trimetazidine is an anti-ischemic agent which selectively inhibits end stage activation of oxidation pathway of 3-ketoacyl coenzyme Athiolase. Trimetazidine has an ability to reduce the accumulation of neutrophil